Innovation and Company Performance - Nursiah; Jamaludin Kamrudin (Universitas Muhammadiyah Palu, 2023)
This paper aims to study and explain the influence of innovation on the performance of medium-sized companies in central Sulawesi by using sampling techniques and non-probability sampling, namely purposive sampling. Data processing uses path analysis. The research results show the influence of innovation directly and indirectly on company performance. This shows the importance of the medium-scale manufacturing industry to be innovative and produce high-quality products to improve company performance.